Two complementary approaches for efficient isolation of Sertoli cells for transcriptomic analysis - Petrusová, Jana; Manning, Jasper; Kubovčiak, Jan; Kolář, Michal; Filipp, Dominik (Frontiers in Cell and Developmental Biology, 2022)
Sertoli cells (SCs) are the only somatic cells that reside in seminiferous tubules of testis. They directly interact with and support the development of germ cells, thus have an indispensable role in the process of spermatogenesis. SCs first appear in a proliferative state and then, with the initiation of the first wave of spermatogenesis, progress to a mature “nurturing” state ¬¬which supports lifelong continuous sperm production. During this development, the SC transcriptome must adapt rapidly as obstacles in SC maturation often result in deficiencies in male fertility. Due to its importance in spermatogenesis, a reliable, rapid, and precise method for the isolation of high purity, viable and unadulterated SC has been largely missing. We have developed an improved method for the preparation of a testicular single cell suspension with two alternative protocols to separate SCs from the rest of the testicular cells by FACS. The first sorting scheme is based on their co-expression of surface specific markers, FSHr and Occludin-1, while the second focuses on the co-staining of SCs with FSHr-specific antibody and Hoechst 33324, which discriminates DNA content of testicular cells. The entire procedure can be completed in less than 3 hours which permits the analysis of the development-related transcriptional profile of these cells. Notably, our comparative study showed that this method resulted in a SC transcriptome that is largely comparable to SCs which were briskly isolated due to their cell-specific expression of fluorescent protein. Interestingly, we also show that SCs sorted as FSHr+Occludin+ cells contained a tangible portion of transcripts from all types of testicular germ cells. Sorting of SCs according to their 2C DNA content significantly reduced the presence of these transcripts, thus seems to be the most suitable approach for accurate determination of the SC transcriptome. We believe that these novel approaches for the isolation of SCs will assist researchers in the elucidation of their function as well as their role in spermatogenesis and disorders related to male infertility.